Effectiveness Of Regional Regulation Number 20 Of 2001 Regarding Regulation Of Street Traders And Seasonal Street Traders In Tarakan City - Fathurrahman, Fathurrahman; Irawan, Aris; Fridayanti, sri (International Journal of Educational Research & Social Sciences, 2023)
This research is motivated by a problem, namely that there is law enforcement against street vendors in Tarakan City, but in the practice of law enforcement, there is a discrepancy or incompatibility with what has been determined in a statutory regulation. The problem is described in two problem formulations, namely: 1. Factors in law enforcement against street vendors in Tarakan City based on Regional Regulation Number 20 of 2001 concerning the Regulation of Street Vendors and Seasonal Street Vendors in Tarakan City, 2. Obstacles to enforcing the law against street vendors in Tarakan City. This study uses empirical research using the collection of legal materials, namely interviews with primary and secondary sources of legal materials, observation, and documentation. The research results obtained in this study are that in substance law enforcement against street vendors in Tarakan City is stipulated in the regional regulation of Tarakan City Number 20 of 2001 concerning Regulation of Street Vendors and Seasonal Street Vendors in Tarakan City is appropriate, and structurally speaking law enforcement carried out by law enforcement, namely the civil service police unit in Tarakan City, has worked according to standard procedures that have been set, But law enforcement is not working as well as it should because there is still a lack of public awareness and understanding of the rules that have been enforced. Street vendors who do not have permission to occupy the location will be dealt with by law enforcement officials in the form of verbal or written warnings to control their merchandise, or they will even be given sanctions according to the provisions of the applicable regional regulations.